2021
DOI: 10.3390/antibiotics10081008
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Alterations Influence Bacterial Growth, Biofilm Production and Antimicrobial Resistance Profiles in Aeromonas spp.

Abstract: Climate change is expected to create environmental disruptions that will impact a wide array of biota. Projections for freshwater ecosystems include severe alterations with gradients across geographical areas. Life traits in bacteria are modulated by environmental parameters, but there is still uncertainty regarding bacterial responses to changes caused by climatic alterations. In this study, we used a river water microcosm model to evaluate how Aeromonas spp., an important pathogenic and zoonotic genus ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
3
0
1
Order By: Relevance
“…The biofilm formation ability of A. hydrophila and its relation to antibiotics susceptibility was evaluated, the results revealed that strong biofilm producer isolates were also resistant to 25% of the antibiotics used in the study (Cephalothin, Amoxicillin and Tetracycline). The isolates with strong biofilm production, which can act as a protective wall against antibiotics, may lead to easy transmission of resistant genes within this protective structure [50,51]. The bacterial isolates that show moderate ability to produce biofilms exhibit intermediate resistance to several types of antibiotics (Gentamycin, Erythromycin and Streptomycin), while the isolates that classified as weak and non-biofilm producer were susceptible to 50% of the studied antibiotics (Nitrofurantoin, Chloramphenicol, Cefixime, Trimethoprim, Ciprofloxacin and Ceftriaxone).…”
Section: Discussionmentioning
confidence: 99%
“…The biofilm formation ability of A. hydrophila and its relation to antibiotics susceptibility was evaluated, the results revealed that strong biofilm producer isolates were also resistant to 25% of the antibiotics used in the study (Cephalothin, Amoxicillin and Tetracycline). The isolates with strong biofilm production, which can act as a protective wall against antibiotics, may lead to easy transmission of resistant genes within this protective structure [50,51]. The bacterial isolates that show moderate ability to produce biofilms exhibit intermediate resistance to several types of antibiotics (Gentamycin, Erythromycin and Streptomycin), while the isolates that classified as weak and non-biofilm producer were susceptible to 50% of the studied antibiotics (Nitrofurantoin, Chloramphenicol, Cefixime, Trimethoprim, Ciprofloxacin and Ceftriaxone).…”
Section: Discussionmentioning
confidence: 99%
“…Lipase production was assessed using Spirit Blue (Difco™, BD Life Sciences, Vaud, Switzerland) agar added with a lipid source, olive oil, and Tween ® 80, using Pseudomonas aeruginosa ATCC ® 27853™ as positive control and a P. aeruginosa Z25.1 clinical isolate from a diabetic foot infection as negative control. Lecithinase activity was determined using tryptic soy agar supplemented with 10% egg yolk emulsion (VWR™, Leuven, Belgium), with P. aeruginosa ATCC ® 27853™ and E. coli ATCC ® 25922™ acting as positive and negative controls, respectively [ 99 , 100 ]. For evaluation of protease production, skim-milk powder (Oxoid, Hampshire, United Kingdom) supplemented with bacteriological agar (VWR™, Leuven, Belgium) was used, with P. aeruginosa ATCC ® 27853™ (positive) and S. aureus ATCC ® 29213™ (negative) being tested as controls [ 99 ].…”
Section: Methodsmentioning
confidence: 99%
“…For evaluation of protease production, skim-milk powder (Oxoid, Hampshire, United Kingdom) supplemented with bacteriological agar (VWR™, Leuven, Belgium) was used, with P. aeruginosa ATCC ® 27853™ (positive) and S. aureus ATCC ® 29213™ (negative) being tested as controls [ 99 ]. Gelatinase activity was detected using Nutrient Gelatin Agar (Oxoid, Hampshire, United Kingdom), using P. aeruginosa Z25.1, a clinical isolate from a diabetic foot infection, and E. coli ATCC ® 25922™, as positive and negative controls, respectively [ 100 ]. Finally, biofilm formation was assessed using Congo red agar plates, composed of BHI broth (VWR™, Leuven, Belgium), bacteriological agar (VWR™, Leuven, Belgium), Red Congo reagent (Sigma-Aldrich, St. Louis, MO, USA), and sucrose, and P. aeruginosa ATCC ® 27853™ (positive) and E. coli ATCC ® 25922™ (negative) as controls.…”
Section: Methodsmentioning
confidence: 99%
“…En Aeromonas se sugiere un efecto bifásico de la temperatura y el pH ambiental; por una parte, el crecimiento de Aeromonas se ve favorecido en ambientes ácidos y este cambio se asoció a la modificación del perfil de resistencia antimicrobiana. Por otro lado, la temperatura afecta la transferencia horizontal de genes y las mutaciones de novo (incluida la recombinación), estos cambios ambientales podrían explicar las diferencias en la resistencia a los antibióticos, en ausencia de determinantes (MGE, mecanismos) de resistencia o presión antimicrobiana en el medio ambiente (66).…”
Section: Resistencia a Antibióticos De Aeromonasunclassified